Study on extension method affected to improve dairy farmer knowledge (Case Study in Cisarua, Bogor) - R W E Lumintang; M Yanti; Hadiyanto Hadiyanto (Faculty of Animal Science, Bogor Agricultural University, 2001)
Study on extension method affected to improve dairy farmer knowledge (Case Study in Cisarua, Bogor)